The Effect on Theatre Nurses for Rendering Perioperative Care to Patients Living with HIV in a South African Tertiary Hospital - Rudzani Ifodia Ngaledzani; Avhatakali Allga Ndou-Mammbona; Azwihangwisi Helen Mavhandu-Mudzusi (AIDS Research and Treatment)
Purpose. The study aimed to gain an in-depth understanding of how theatre nurses are being affected when they render perioperative care to patients living with HIV in a South African tertiary hospital. Background. There is a scarcity of studies that focus solely on the wellbeing of theatre nurses who render perioperative care to HIV patient due to the ramifications of the nurses’ fear of contracting HIV. Patients living with HIV often receive substandard care. Objectives. To establish how theatre nurses are being impacted when rendering perioperative care to patient living with HIV, the study followed a qualitative approach using an interpretative phenomenological analysis design. Data were collected through in-depth individual interviews from ten theatre nurses who were purposively selected according to specific criteria. They voluntarily agreed to participate. An interpretive phenomenological analysis framework was used to analyse the data. Two main themes emerged from the data analysis, namely, the negative effect on nurses’ wellbeing and the impact that it had on them professionally. Results. The study revealed that the perioperative care of patients living with HIV had a negative impact on physical, mental, and social wellbeing of theatre nurses. Their compromised wellbeing in turn led to poor patient care, which put nurses at risk of losing their jobs and even potentially having to face litigation. The study further indicated that nurses did not receive psychological support from the management which further affected their health and professional performance. Conclusion. The study proposes that theatre nurses rendering perioperative care to people living with HIV should receive proper training and support; staff shortages should also be addressed. There is also an urgent need for appropriate and sufficient protective equipment. Such changes will be essential in order to mitigate the negative impact that their jobs have on their wellbeing and on them in their professional capacity.